Relações entre aspectos ortográficos e fonético-fonológicos de fonemas oclusivos - Pezarini, Isabela De Oliveira; Vaz, Suellen; Paschoal, Larissa; Chacon, Lourenço (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
PURPOSES: to describe the children's orthographic performance - regarding to the record of plosive consonants from the Brazilian Portuguese; check if the accent influences the occurrence of mistakes inside the words; and classify the pattern of the mistakes distribution. METHODS: 210 text productions referred to 14 thematic proposals were analyzed, they were collected during the year 2001, when the individuals attended the First grade of Primary School. To describe the children's performance, for the first objective, the data were divided in Hits and Mistakes; for the second objective, the mistakes were classified according to their occurrence in accented and non-accented syllables, and, finally, for the third objective, the mistakes were subclassified in omissions, orthographic and phonological mistakes. The phonological mistakes were even subdivided, according to their occurrence inside and outside the occlusive class. RESULTS: for the first objective, 5.746 possibilities of occurrence of plosive consonants in a position of simple syllable onset were found, with a high amount of hits; for the second objective, it was observed a higher occurrence of mistakes in non-accented syllables; and finally, for the third objective, it was possible to observe the predominance of phonological mistakes, followed by omissions and by orthographic mistakes, both inside the non-accented syllables and the accented ones. Still according to the third objective, in the phonological mistakes, a higher occurrence of mistakes inside the class was observed and, again, no accent influence. CONCLUSION: the importance of the phonetic-phonological aspects analysis in the acquisition of child orthography is highlighted, as well as the relevance of the distribution of hits and mistakes in the orthographic performance.

OBJETIVOS: descrever o desempenho ortográfico de crianças - quanto ao registro de consoantes oclusivas do Português Brasileiro; verificar se a acento influencia a ocorrência de erros no interior das palavras; e classificar o padrão da distribuição dos erros. MÉTODOS: foram analisadas 210 produções textuais referentes a 14 propostas temáticas, coletadas durante o ano de 2001, quando os sujeitos cursavam a 1ª série do Ensino Fundamental. Para descrever o desempenho das crianças, para o primeiro objetivo, os dados foram divididos em Acertos e Erros; para segundo objetivo, os erros foram classificados em sílabas acentuadas e não-acentuadas, e, por fim, para o terceiro objetivo, os erros foram subclassificados em omissões, erros ortográficos e erros fonológicos. Os erros fonológicos foram subdivididos, ainda, conforme ocorressem dentro e fora da classe. RESULTADOS: para o primeiro objetivo, encontraram-se 5.746 possibilidades de ocorrência de consoantes oclusivas na posição de ataque silábico simples, com maior quantidade de acertos; para o segundo objetivo, observou-se maior ocorrência de erros em sílabas não-acentuadas; e por fim, para o terceiro objetivo, foi possível observar predomínio de erros fonológicos, seguidos pelas omissões e pelos erros ortográficos, tanto no interior das sílabas não-acentuadas quanto das acentuadas. Ainda conforme o terceiro objetivo, nos erros fonológicos, observou-se sua maior ocorrência dentro da classe; e novamente, não-influência do acento. CONCLUSÃO: conclui-se, então, a importância da análise dos aspectos fonéticos-fonológicos na aquisição da ortografia infantil, bem como a relevância da distribuição dos acertos tanto como dos erros.
Relations between orthographic and phonetic-phonological aspects of plosive phonemes
Keywords: Handwriting; Language Development; Child; Phonetics; Linguistics; Escrita Manual; Desenvolvimento da Linguagem; Criança; Fonética; Linguística